European retrospective study of real‐life haemophilia treatment. Issue 1 (20th October 2016) - Berntorp, E.; Dolan, G.; Hay, C.; Linari, S.; Santagostino, E.; Tosetto, A.; Castaman, G.; Álvarez‐Román, MT.; Parra Lopez, R.; Oldenburg, J.; Albert, T.; Scholz, U.; et al.
Abstract : Introduction: Haemophilia treatment varies significantly between individuals, countries and regions and details of bleed rates, factor consumption and injection frequency are often not available. Aim: To provide an overview of the FVIII/FIX treatment practice and outcome for patients with haemophilia A (HA) or haemophilia B (HB) across Europe. Methods: Non‐interventional, 12‐month retrospective study where anonymized data were retrieved from haemophilia centres/registers in Belgium, France, Germany, Italy, Spain, Sweden and the United Kingdom. Male patients (all ages) receiving coagulation factor treatment 24 months prior to the study, with basal FVIII/FIX levels ≤5 IU dL −1, without inhibitors, were included. Data were summarized descriptively. Results: In total, 1346 patients with HA and 312 with HB were included in the analysis; 75% and 57% had severe disease (FVIII/FIX < 1 IU dL −1 ) respectively. Prophylaxis was most common for severe haemophilia, especially for children, whereas on‐demand treatment was more common for moderate haemophilia in most countries. The mean (SD) prescribed prophylactic treatment ranged from 67.9 (30.4) to 108.4 (78.1) (HA) and 32.3 (10.2) to 97.7 (32.1) (HB) IU kg −1 per week, across countries. Most patients on prophylaxis were treated ≥3 times/week (HA) or two times/week (HB). The median annual bleeding rate (ABR) for patients on prophylaxis ranged from 1.0 to 4.0 for severe HA, and from 1.0 to 6.0 for severe HB, while those with moderate haemophilia generally had slightly higher ABRs. Median ABRs for on‐demand‐treated severe HA ranged from 4.5 to 18.0, and for HB, 1.5 to 14.0. Conclusion: Treatment practice varied greatly between centres and countries and patients treated on‐demand and prophylactically both experienced bleeds, emphasizing the need for further optimization of care.